Effects of Extraoral Suction on Droplets and Aerosols for Infection Control Practices - Hidenobu Senpuku (Dentistry Journal, 2021)
Dental professionals are at increased risk of being infected with airborne pathogens such as SARS-CoV-2 because they are often exposed to droplets/aerosols production during dental treatment. To scientifically clear the effects of extraoral and oral suctions on the droplets and aerosols produced by dental treatments using an ultrasonic scaler was analyzed. The adenosine triphosphate and bacteria in droplets and aerosols produced during simulated scaling were quantitatively observed by reactions with luciferin/luciferase and incubation in culture plates to grow bacteria, respectively. The protection against spreading droplets and aerosols by oral and extraoral suctions was recognized, and the areas were limited to the left and posterior sides of the dental chair head when a right-handed dentist and dental hygienist performed scaling. Extraoral suction is a very useful tool for reducing the infection risk of COVID-19 in dental care, but the effective area is limited depending on physical characteristics of dentist and dental hygienist.